Los determinantes demostrativos y su valor endofórico en el español hablado en Costa Rica. - Sánchez Avendaño, Carlos (2012)
In this article the endophoric and deictic values of the demostratives 'este', 'ese' and 'aquel' in Costa Rican spoken Spanish are described. For each case, factors motivating their ocurrence are identified, along with the notions determining their discourse reference. Finally, the semantic values of their distribution are examined.